1986
DOI: 10.1002/ajmg.1320230151
|View full text |Cite
|
Sign up to set email alerts
|

Population incidence and segregation ratios in the Martin‐Bell syndrome

Abstract: A clinical and cytogenetic study of children attending schools for the educationally handicapped has been carried out in the City of Coventry. As a result of this an estimate of the population incidence of the Martin-Bell syndrome among schoolchildren has been made. Among school-boys the incidence of mental retardation due to the fra (X) was found to be 0.73 per 1000 and among schoolgirls 0.48 per 1000. The overall prevalence is 0.61 per 1000. Genetic and cytogenetic analysis of 14 families ascertained in an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0
2

Year Published

1988
1988
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(55 citation statements)
references
References 6 publications
2
51
0
2
Order By: Relevance
“…FMR1, which contains two KH domains [4,5] is of particular interest since mutations of the gene cause fragile X syndrome, the most frequent cause of mental retardation in humans, affecting 1 in 1250 males and 30% of female carriers [6][7][8]. The KH domain is sometimes present in large numbers: 8 in yeast scpl60 and 14 in vigilin, the highest number so far [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…FMR1, which contains two KH domains [4,5] is of particular interest since mutations of the gene cause fragile X syndrome, the most frequent cause of mental retardation in humans, affecting 1 in 1250 males and 30% of female carriers [6][7][8]. The KH domain is sometimes present in large numbers: 8 in yeast scpl60 and 14 in vigilin, the highest number so far [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…FXS (FXS) is one of the most prevalent genetic causes of MR, representing the most frequent form of inherited severe cognitive deficit, second only to Down syndrome as a genetic cause of MR. It is estimated that the FXS affects approximately 1 in 2,500 individuals (1)(2)(3)(4).The syndrome is inherited as an X-linked dominant trait with reduced penetrance 80% in males and 30% in females (5). According to studies conducted in Iran the frequency of FXS have been reported to be 63% (6).…”
Section: Introductionmentioning
confidence: 99%
“…Its worldwide prevalence is about 1 in 3600 men and 1 in 8000 women (Turner et al, 1996;Kooy et al, 2000), and it is considered of great epidemiologic importance among men with mental disabilities (Webb et al, 1986). FMR1 mutation is characterized by increased trinucleotide CGG repetitions in the 5'-untranslated region of the gene (Fu et al, 1991).…”
Section: Introductionmentioning
confidence: 99%